(3GdeYGedI GdLRGFjI ddCMOGK aj GdbGfhf GdEeGQGJj (B:s "(3OQGSI ebGQfI(B" /s - (3TjNI eMeO NdaGf GdjQhGf GdTGeSj(B.s; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3Ef eTcdI GfMQGa GdCMOGK dG oJYO hdjOI gPG GdYUQ, hEf GNJdaJ aj Gdce hGdcja ef YUQ dBNQ, hef eLJeY dBNQ(B. (3ceG Cf GdLQjeI hGdELQGe aj GdeLJeY dG jYOGf ef GdXhGgQ MOjKI GdYgO, Hd YGfJ efgG GdeLJeYGJ GdbOjeI, hYQaJgG GdJTQjYGJ aj eNJda GdYUhQ, hTQYJ dgG GdbhGfjf defY GQJcGH GdCaYGd GdJj JTcd NWhQI Ydi GdeLJeY hTHcI YdGbGJg, hPdc efP Cf TQY GdEfSGf aj GdYjT aj fWGb GdYTjQI hGdbHjdI, QZe hLhO SdWGf QSej, cGdTQWI hGdeMGce hGdSLhf, aGdeLJeYGJ de JNd ef GdLQjeI, agj fJjLI dGReI dMjGI GdHTQ heG jKhQ Hjfge ef JfGRY hJOGaY aj GdeUGdM, hJfGaS Ydi ETHGY GdMGLGJ(B. (3hYdi GdQZe ef Cf XGgQI GdELQGe eG RGdJ ehVhY GgJeGe YdeGA GdbGfhf hGdGLJeGY deG JKjQg ef GVWQHGJ aj GdYdGbI GdEfSGfjI, hEgOGQ ddbje hGdYGOGJ GdSGFOI, hJgOjO dSdWI GdOhdI hGdbGfhf, hbO GJNP gPG GdJWhQ CTcGkdG eNJdaI JeKdJ aj GdJRGjO GdePgd aj fSH GfMQGa GdCMOGK(B. (3hQZe GdJMhd GdLPQj aj CSdhH eYGedJge Hjf GdbOje hGdMOjK, abO Md aj GdSjGSGJ GdJTQjYI GdMOjKI efgL jbhe Ydi GdJbhje hGdEUdGM hGdJCgjd ddCMOGK, HOkdG ef GdefgL GdbOje GdPj cGf jbhe Ydi GdYbhHGJ GdLeGYjI hGdLSOjI HGdZI GdTOI hGdbShI, abOjeG GYJHQ GdMOK GdefMQa eLQkeG, hCfg jSJMb GdYbGH hdG SHjd dEUdGMg EdG HGdHJQ MJi dG jUGH GdeLJeY HGNJdGd JhGRfg, CeG GdeLJeYGJ GdMOjKI aJfXQ Edi GdCMOGK ZGdkHG Ydi Cfge VMGjG XQha GLJeGYjI COJ Hge Edi GdGfMQGa hShA GdJcja, hCf JgjFJge hJOYjege HGdebheGJ GdUGdMI geG GdMaGX GdMbjbi dbhGege hGfWdGbge fMh CgOGa GLJeGYjI HfGAIs
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2022s
(3HHdjhLQGajG(B: (3U(B. 410-447.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdbGfhf GdGeGQGJjs; (3GdLGfMjfs; (3eQGMd GdeSFhdjIs; (3GdJbfjGJ GdMOjKIs; (3GdeYGedI GdLRGFjIs; (3eMGce GdGMOGKs; (3GdeDSSGJ GdYbGHjIs; (3JTQO GdGMOGKs; (3GdJOGHjQ GdGMJQGRjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs